Availability, Uniqueness and Perceived Value of Bachelor of Science in Pharmaceutical Sciences (BSPS) Programs in the United States - Rabaa M. Al-Rousan; Fadi M. Alkhateeb; Michael Veronin; David A. Latif; Marea Dodd (MDPI AG, 2013)
We describe the uniqueness of the Bachelor of Science in Pharmaceutical Sciences (BSPS) degree and the factors that contribute to this uniqueness. A total of 18 colleges and schools that offer a BSPS were identified in the literature and compared. A review of the current literature and university websites was conducted in order to compare and contrast the different BSPS programs. BSPS program directors' perceptions were evaluated through a 14-item online survey instrument. Of the 16 programs surveyed, seven (43.8%) responded to the survey. The respondents agreed that most of the BSPS graduates are placed (from the highest to the lowest) at pharmacy school, postgraduate education and in the pharmaceutical industry. This is a timely review of coursework, program lengths and job opportunities for graduates of the BSPS. Currently, the BSPS programs have yet to receive a large amount of attention, but the importance in pharmaceutical education cannot be denied.